Analaisis Pengaruh Insentif Dan Motivasi Terhadap Kinerja Dan Loyalitas Agen Perisai BPJSTK (Cabang Utama Surabaya) - Alifya Putri Samudera; Minto Waluyo (Pusat Riset dan Inovasi Nasional, 2023)
BPJS Employment launched an agency system, the National Social Security Drive or named Perisai. Through the Perisai agency system, BPJS Employment seeks to expand the scope of membership. There was a policy change in February 2022 so research was carried out to analyze the influence of incentive and motivation programs on the performance and loyalty of shield agents. The analysis in this research carried out questionnaires distributed to 40 shield agents and processed using the Partial Least Square method using Smart PLS. This research showed that the incentive program influenced performance, while motivation variables did not influence performance, and performance influenced the loyalty of the shield agent's performance.